Practical neurocounseling : connecting brain functions to real therapy interventions - Russell-Chapin, Lori A.; Pacheco, Nicole; DeFord, Jason A. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Practical Neurocounseling demonstrates the importance of considering brain health in counseling, showing mental health professionals how to understand and assess the functioning of different parts of the brain without sophisticated software or intensive training. More than just a collection of techniques, Practical Neurocounseling is a valuable guide for clinicians interested in the relationship between brain activity and behavior. It's also an ideal book for professors and students in any neurocounseling course and for clinicians working in talk therapy"--
OCLC-licensed vendor bibliographic record.
Keywords: Counseling psychology; Neuropsychology; Neurosciences; Brain; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health